1968
DOI: 10.1002/1097-0142(196805)21:5<964::aid-cncr2820210521>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of enzymes in human vaginal fluid.Relevance to the Diagnosis of Cervical Cancer

Abstract: Pooled material obtained by vaginal irrigation of women with gynecologic conditions has been fractionated into cellular and extracellular phases to determine the best method of applying enzyme assays in the diagnosis of cancer of the cervix uteri. Ribonuclease, when measured in the homogenized cellular material, was elevated by more than 400% in the group with cancer. Estimations utilizing the extracellular plasma and high speed supernatants prepared from the homogenate were unpromising. β‐glucuronidase was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1968
1968
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Clinical details of the patients without cancer exceeding this arbitrary level (false-positives) and of the cancer patients whose values fall below this level (false-negatives) are given in Table 111. The mean value for the 6 pre-menopausal subjects was 880 while the mean for the 14 postmenopausal subjects was Previously, using pooled material from 5 to 10 subjects, we found excellent discrimination between patients with and without cervical cancer when the ratio between extracellular and intracellular RNAase specific activities was calculated (Goldberg et al, 1968). When the phase of the cycle was taken into account further support for this view was obtained in these three cases.…”
Section: Thesupporting
confidence: 51%
See 3 more Smart Citations
“…Clinical details of the patients without cancer exceeding this arbitrary level (false-positives) and of the cancer patients whose values fall below this level (false-negatives) are given in Table 111. The mean value for the 6 pre-menopausal subjects was 880 while the mean for the 14 postmenopausal subjects was Previously, using pooled material from 5 to 10 subjects, we found excellent discrimination between patients with and without cervical cancer when the ratio between extracellular and intracellular RNAase specific activities was calculated (Goldberg et al, 1968). When the phase of the cycle was taken into account further support for this view was obtained in these three cases.…”
Section: Thesupporting
confidence: 51%
“…The dependence of enzyme activity upon the menstrual history operates in a manner contrary to that shown by p-glucuronidase Fishman et al, 1951). We have already shown that the presence of blood reduces the RNAase activity of vaginal fluid (Goldberg et al, 1968), and pus cells may act in a similar manner by virtue of their high content of nuclease inhibitors (Maney et al, 1960). The false-negative rate of ten per cent is better than that possible with pglucuronidase and a-mannosidase estimations, and compares favourably with most published series utilizing 6-phosphogluconate dehydrogenase assay, though it must be stressed that the diagnosis had already been established in all the cancer patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Among these secreted compounds are mucins, in particular MUC4, MUC5A/C and MUC8, covering the vaginal wall with a mucus layer (10). The enzymatic activity in the vagina is comparatively lower than in the gastrointestinal tract but there is still a wide range of enzymes present such as nucleases, lysozymes and esterases (11,12). Women of reproductive age produce fluid at a rate of approximately 6 mL/day, with 0.5-0.75 mL continually present in the vagina.…”
Section: Vaginal Anatomy Histology and Physiologymentioning
confidence: 99%